Caribbean regional profile 2007 (JTZ Publishing CumanaTT, 2006)
Provides political and economic information and social factors influencing business trends within the region's 38 countries including the Florida region. Aims to provide insightful analysis of the factors affecting the region's business community and potential for investment.
Keywords: YEARBOOKS